Bevarandeetologi : etologins roll i bevarandeprojekt - Thelander, Frida (SLU/Dept. of Animal Environment and Health (until 231231), 2016)
To understand and manage animal behavior have always been of interest in wildlife management, especially in captive breeding and pest control. In the 1990’s however ethologists for the first time began to generate new strategies for conservation and management of animals, which evolved into a new field, conservation behavior. Unfortunately, the area has not yet had great success, presumably due to conservation biologists having difficulties seeing how ethology can promote real-life conservation problems. Other known dilemmas in integrating the two fields of conservation and ethology is the absence of a clear framework and problems in publishing of articles. Conservation journals usually reject ethological articles since they don’t show an immediate impact on population dynamics, and ethological journals often reject conservational articles because of a lack of theoretical background. Despite this, multiple studies show that integrating ethology in conservation can increase the success of conservation projects. Behavior is clearly an important part of the animal’s survival and reproductive success, and therefore affect both population structure, demography and social structure. Knowledge of animal’s behavior has the potential to increase our understanding of how populations survive in fragmented landscapes, how populations react to exploitations, the susceptibility to diseases, population monitoring and modelling, as well as animal’s reproduction in captivity and re-introductions. The aim of this study is to investigate the role of conservation behavior today. I also mean to illustrate the effects ethology can have on conservation projects, as well as discuss the future of conservation behavior. This study was performed as a literature review. The results showed that conservation behavior can benefit both in situ- and ex situ-projects, monitoring of wild populations, captive breeding, re-introductions and translocations, as well as counteraction of exploitation and animal-human conflicts. The results also show that the field of conservation behavior already is cited in journals, but have to be established more to play an important role in practical conservation projects. Inter alia, seven propositions of how to make ethology establish in conservation is presented and discussed. Two different frameworks for behavior conservation is also outlined.